Occurrence and Fate Analysis of Mycotoxins in Maize During the Post-Harvest Period - Yajie Zheng; Wenfu Wu; Changpo Sun; Hujun Liu; Jianpeng Dou (Toxins)
The consumption of agricultural products contaminated with mycotoxins poses a significant threat to the health of both humans and animals. Maize frequently becomes contaminated with toxic fungi while it is still growing in the field. Therefore, more proactive measures should be implemented to reduce mycotoxin levels during the storage and processing of maize after harvest. This article analyzes the prevalent mycotoxins found in maize, specifically aflatoxins, ochratoxins, trichothecenes, fumonisins, and zearalenone. The study provides a comprehensive analysis of the occurrence of mycotoxins in maize during storage, as well as fate analysis of them during processing. It summarizes the impacts of storage time, environmental conditions, storage methods, and agricultural practices on mycotoxin occurrence during storage in the post-harvest period. Furthermore, the different distribution of mycotoxins across various fractions during both dry- and wet-milling processes in the post-harvest processing period is analyzed. Additionally, the strategies to control mycotoxins in maize are also proposed during the post-harvest period. This review offers valuable insights for future research on mycotoxin contamination in maize during the post-harvest period.